Single Candidate and Empty Box Lampung 2024: In the West Tulang Bawang Regional Election and the West Lampung Regional Election - Irawan Riyanto, Pandu; Abdullah, Yumiriyah; Yudha Ikhwan Pradana, Nanda (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study examines the phenomenon of single candidates in the 2024 regional elections in Tulang Bawang Barat and Lampung Barat. The two regencies represent the increasing phenomenon of single candidates in Indonesia. Using a desk study method, this research analyzes data from scientific articles and online news sources. Findings show that the dominance of political dynasties is a key factor, with candidates in both regions having blood ties to former regional heads. Political parties have failed in their cadre function and instead support resource-rich candidates from outside their party, leading to decreased political competition and public participation. As a result, local democracy regresses, with limited electoral choices and weakened democratic institutions. In this context, the active role of citizens becomes very important to maintain the sustainability of existing democratic institutions. Without public involvement and pressure for accountability, democratic structures become vulnerable to stagnation and elite capture in local elections.